1995
DOI: 10.1104/pp.108.1.399
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Seed Fatty Acid Composition by an Ethyl Methanesulfonate-Induced Mutation in Arabidopsis thaliana Affecting Diacylglycerol Acyltransferase Activity

Abstract: In characterizing the enzymes involved in the formation of very long-chain fatty acids (VLCFAs) i n the Brassicaceae, we have generated a series of mutants of Arabidopsis thaliana that have reduced VLCFA content. Here we report the characterization of a seed lipid mutant, AS1 1, which, in comparison to wild type (WT), has reduced levels of 20:l and 18:l and accumulates 18:3 as the major fatty acid in triacylglycerols. Proportions of 18:2 remain similar to WT. Cenetic analyses indicate that the fatty acid pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
257
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(280 citation statements)
references
References 33 publications
16
257
1
2
Order By: Relevance
“…This is consistent with gene expression data, which show that SDP1 transcripts are greater than 10-fold more abundant in vegetative tissues than SDP1L (Kelly et al, 2011). TAG synthesis in Arabidopsis seeds relies jointly on the activities of DGAT1 (Katavic et al, 1995) and PDAT1 ). However, analysis of dgat1 and pdat1 mutants suggests that DGAT1 is quantitatively more important ).…”
Section: Tag Accumulation In Sdp1 Roots Is Greater Than In Several Otsupporting
confidence: 90%
See 3 more Smart Citations
“…This is consistent with gene expression data, which show that SDP1 transcripts are greater than 10-fold more abundant in vegetative tissues than SDP1L (Kelly et al, 2011). TAG synthesis in Arabidopsis seeds relies jointly on the activities of DGAT1 (Katavic et al, 1995) and PDAT1 ). However, analysis of dgat1 and pdat1 mutants suggests that DGAT1 is quantitatively more important ).…”
Section: Tag Accumulation In Sdp1 Roots Is Greater Than In Several Otsupporting
confidence: 90%
“…Finally, analysis of sdp1 dgat1 and sdp1 pdat1 double mutants showed that TAG accumulation in sdp1 roots is largely dependent on DGAT1 function but that PDAT1 is also required. It has already been established that DGAT1 is necessary for normal TAG synthesis in seeds, seedlings, and leaves of Arabidopsis (Katavic et al, 1995;Lu et al, 2003;Slocombe et al, 2009), but pdat1 has not previously been shown to have a TAG phenotype. Recently, a third acyltransferase (DGAT3), with specificity toward polyunsaturated fatty acids, has also been shown to play a role in TAG synthesis in Arabidopsis seedlings (Hernández et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the characterization of this gene to date has been focused on determining its effect on seed oil accumulation and the fatty acid composition of TAG in seed oil. To this end, seed-specific mutants have been analyzed (Katavic et al, 1995;Zou et al, 1999;Jako et al, 2001), and among the findings from these studies is the fact that dysfunctional DGAT1 protein results in a decrease in stored TAG and altered TAG fatty acid composition (Katavic et al, 1995). Overexpression of DGAT1 in Arabidopsis seeds engenders an increase in seed size and oil content, suggesting that DGAT catalyzes the ratelimiting step in TAG biosynthesis (Jako et al, 2001).…”
mentioning
confidence: 99%